Respuesta :

3x -  1y =   4 ⇒ 9x -  3y = 12
1x + 3y = 11 ⇒ 1x + 3y = 11
                               10x = 23
                                10     10
                                   x = 2.3
                            3x - y = 4
                      3(2.3) - y = 4
                          6.9 - y = 4
                        - 6.9       - 6.9
                                 -y = -2.9
                                 -1     -1
                                  y = 2.9
                            (x, y) = (2.3, 6.9)